Mario Samper: Pioneer of an Agrarian History Tradition - Picado Umaña, Wilson (2019)
This article assesses the academic work of the Costa Rican historian Mario Samper. It analyzes the evolution of his research on Agrarian History, focusing in his studies on peasant-farmer settlement and peasant economy. Finally, it reviews his research on the history of coffee-growing areas in Costa Rica, Central America and Latin America.